Examination of Intercultural Sensitivity Levels of Nursing Students - KABU HERGÜL, Filiz; GÖK, Fadime; İPİÇÜRÜK, Hilal Gizem (MAS Journal of Applied Sciences, 2022)
The aim of this descriptive study was to determine the intercultural sensitivity levels of nursing students.The universe of the study consisted of all students (n=811) studying in the nursing department of a University’shealth sciences faculty in the 2019-2020 spring semester. All students (n=360) who agreed to participate in thestudy without sampling were included in the sample. Data were collected with "Student Descriptive InformationForm" and "Intercultural Sensitivity Scale. Data were evaluated with number, percentage, mean, standarddeviation, Independent Samples t-test, One-Way Anova, Mann Whitney-U and Kruskal Wallis tests. The meanage of the students was 20.01±1.41 and 81.4% were women. When the descriptive characteristics of the studentsand the Intercultural Sensitivity Scale mean score were compared, It was determined that there was a statisticallysignificant difference between gender and having friends from different cultures. It was observed that femalestudents were more respectful to cultural differences, while males were more self-confident in interculturalinteraction. It was determined that students who have friends from different cultures have higher participation inintercultural interaction, self-confidence in intercultural interaction, enjoyment of intercultural interaction andintercultural sensitivity. It was determined that the students included in the study had a moderate level ofintercultural sensitivity in general. In addition, when viewed according to the scale sub-dimension; It wasdetermined that while the students used the sub-dimension of participating in intercultural interaction the most,they used the sub-dimension of paying attention to intercultural interaction the least.